Green Product Awareness and Green Purchasing Behavior of Generation Z: The Case of State Universities in Region 4A, Philippines - Advincula, Geraldine Batilo; Cayabat, Chona (Faculty of Economics, Universitas Sriwijaya, 2024)
This study aims to analyze the demographic profile of business administration students in terms of age, gender, and university year level, assess their awareness of green products, and evaluate their green purchasing behavior. Key variables examined include environmental awareness, knowledge, concern, perceived consumer effectiveness and responsibility, social influence, willingness to pay, eco-label, and attitude. The study also explores the relationship between green product awareness and purchasing behavior, and assesses demographic profile differences in purchasing behavior. A descriptive-correlational design was employed, statistical tools such as frequency and percentage, weighted arithmetic mean, Kruskal-Wallis test, and Spearman rho correlation were used to analyze the data. Findings reveal that green product awareness correlates positively with environmental awareness, knowledge and social influence that shows a moderate correlation. Variables like environmental concern, perceived consumer effectiveness, responsibility, willingness to pay, eco-label, and attitude towards green purchasing exhibit weaker relationships. Age and gender do not significantly influence the variables, though year level impacted environmental concern and attitudes.